Evaluation of new-onset atrial fibrillation using continuous patch monitor in patients undergoing transcatheter aortic valve replacement. (25th November 2020) - Miki, T; Senoo, K; Okura, T; Sato, Y; Shiraishi, H; Shirayama, T; Matoba, S
Abstract: Background: Transcatheter aortic valve replacement (TAVR) has emerged as an important therapeutic option among intermediate- and high-risk patients with symptomatic severe aortic stenosis. Heart rhythm disorders frequently complicate TAVR, particularly atrial fibrillation (AF), which can affect >40% patients undergoing the procedure. There is wide variation in rates of new-onset AF (NOAF) following TAVR across the initial pivotal randomized trials and observational studies, but burden of AF in each patient is not well known. The aim of this study is to evaluate AF burden detected by continuous patch ECG monitor (WR-100; Fukuda-Denshi, Tokyo, Japan) in patients after TAVR. Method: Among KPUM-TAVR cohort, 58 consecutive patients (mean age:85.5±5.5, 44 females) kept recording continuous patch ECG monitor for 14 days after the procedure of TAVR. We excluded 11 patients with ECG indicating AF before procedure (paroxysmal AF 5, persistent AF 6). Finally, 47 eligible patients were selected according to the study criteria. AF was defined as a presence of AF more than 30sec on ECG monitor. The incidence and burden of NOAF was assessed. Results: We identified 9 of 47 patients (19.1%) who developed NOAF (94% of transfemoral access patients, 6% of non- transfemoral access patients). Patients developing NOAF and had higher Society of Thoracic Surgeons risk scores (5.9±3.8 vs 9.9±6.3 p=0.0187). AF was first observed from day1 to day13. Despite having a median CHA2DS2-VASc score of 5 (25th and 75th percentile: 5 to 6), only 33% of patients with NOAF were given oral anticoagulation during the follow-up. Conclusion: By using continuous patch ECG monitor, NOAF can be identified in 19.1% of patients after TAVR, with wide variety of first onset of AF. Given the clinical significance of post-TAVR AF, additional studies are necessary to describe the optimal management strategy in this high-risk population. Funding Acknowledgement: Type of funding source: None